Hybrid Histidine Kinase WelA of Sphingomonas sp. WG Contributes to WL Gum Biosynthesis and Motility - Li, Hui; Chen, Mengqi; Zhang, Zaimei; Li, Benchao; Liu, Jianlin; Xue, Han; Ji, Sixue; Guo, Zhongrui; Wang, Jiqian; Zhu, Hu (Frontiers in Microbiology, 2022)
Sphingomonas sp. WG produced WL gum with commercial utility potential in many industries. A hybrid sensor histidine kinase/response regulator WelA was identified to regulate the WL gum biosynthesis, and its function was evaluated by gene deletion strategy. The WL gum production and broth viscosity of mutant ∆welA was only 44% and 0.6% of WT strain at 72 h. The transcriptomic analysis of differentially expressed genes showed that WelA was mapped to CckA; ChpT and CtrA in the CckA-ChpT-CtrA pathway was up-regulated. One phosphodiesterase was up-regulated by CtrA, and the intracellular c-di-GMP was decreased. Most genes involved in WL gum biosynthesis pathway was not significantly changed in ∆welA except the up-regulated atrB and atrD and the down-regulated pmm. Furthermore, the up-regulated regulators ctrA, flaEY, flbD and flaF may participate in the regulation of flagellar biogenesis and influenced motility. These results suggested that CckA-ChpT-CtrA pathway and c-di-GMP were involved in WL gum biosynthesis regulation. This work provides useful information on the understanding of molecular mechanisms underlying WL gum biosynthesis regulation.